Solastalgic Landscapes: Prospects of Relocation in Coastal Louisiana - Simms, Jessica R. Z. (Frontiers in Environmental Science, 2021)
Globally, rapid and slow-onset socio-environmental coastal disasters are prompting people to consider migrating inland. Climate change is exacerbating these disasters and the multi-faceted causal contributing factors, including land loss, livelihood shifts, and disintegration of social networks. Familiar with ongoing disruptive displacements, coastal Louisiana residents are now increasingly compelled to consider permanent relocation as a form of climate adaptation. This paper elicits and analyzes coastal Louisiana residents’ perceptions of socio-environmental changes as they pertain to relocation as adaptation and the precariousness of place, both biophysically and culturally. It investigates how these external mechanisms affect relocation decisions, and empirically expand on how these decision-making processes are affecting residents internally as well. Research methods include semi-structured interviews with coastal Louisiana residents, participant observation, and document analysis. The paper integrates literature on environmental migration, including climate-driven; regional studies on Louisiana, and disasters, with empirical, interview-based research. It is guided by theoretical insights from the construct “solastalgia,” the feeling of distress associated with environmental change close to one’s home. The findings suggest that residents’ migration decisions are always context-dependent and location-specific, contributing to a broader understanding of coastal residents’ experiences of staying or going.